Publication Analysis on Supply and Demand Research: Mapping Future Research - Febriza, Milla; Rozalinda, Rozalinda; Zulvianti, Nora (Denisya Smart Consulting, 2025)
This study aims to map and analyze the development trends of research on the topic of